2015
DOI: 10.1186/s13059-015-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual differences in the gene content of human gut bacterial species

Abstract: BackgroundGene content differences in human gut microbes can lead to inter-individual phenotypic variations such as digestive capacity. It is unclear whether gene content variation is caused by differences in microbial species composition or by the presence of different strains of the same species; the extent of gene content variation in the latter is unknown. Unlike pan-genome studies of cultivable strains, the use of metagenomic data can provide an unbiased view of structural variation of gut bacterial strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
157
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 67 publications
11
157
1
1
Order By: Relevance
“…In contrast, four of the discriminant genes were not detectable in the outlier persister with high levels of native B. longum (subject D). This analysis suggests interindividual variability of genes among the resident B. longum population, consistent with recent findings in several dominant species present in the human gut (Zhu et al, 2015).…”
Section: Genes That Predict Colonization Show Inter-individual Variatsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, four of the discriminant genes were not detectable in the outlier persister with high levels of native B. longum (subject D). This analysis suggests interindividual variability of genes among the resident B. longum population, consistent with recent findings in several dominant species present in the human gut (Zhu et al, 2015).…”
Section: Genes That Predict Colonization Show Inter-individual Variatsupporting
confidence: 91%
“…However, B. longum levels did not explain the findings in all subjects, in that some persisters had relatively high levels of B. longum. Because traits that define niches and competitive interactions are not necessarily phylogenetically conserved in bacteria, and can differ substantially within the same bacterial species (Zhu et al, 2015), we used WMS data and compared the abundance of genes identified to belong to the species B. longum, at pretreatment baseline between persisters and non-persisters. A Wilcoxon test resulted in 70 genes with differential abundance between persisters and non-persisters ( Figure 3F; Table S4).…”
Section: Community Membership Differs In Persisters and Non-persistersmentioning
confidence: 99%
“…However, different strains of the same species can differ significantly in their gene content (Greenblum et al 2015;Zhu et al 2015) and single-nucleotide polymorphisms (SNPs) (Schloissnig et al 2013;Kashtan et al 2014;Lieberman et al 2014). These strain-level differences are important for understanding microbial evolution, adaptation, pathogenicity, and transmission.…”
mentioning
confidence: 99%
“…Estudos recentes buscam o mapeamento desse microbioma, para, de forma unificada e específica, centrar ações terapêuticas cada vez mais na especificidade das lesões e doenças, evitando resistência microbiana, sobretratamentos, superdoses medicamentosas e utilização de medicamentos pouco ativos ou inativos para dada patologia 3 . Os probióticos estão no centro dessas descobertas, sendo os principais vetores para promoção de ação nos diferentes microrganismos endógenos humanos, visando ao desenvolvimento do processo de saúde no hospedeiro 4,5 . Esses agentes, que podem estar presentes em alimentos e também em alguns produtos específicos, têm sido utilizados em benefício da saúde e, em alguns casos, no tratamento adjuvante de algumas doenças.…”
Section: Introductionunclassified